2005
DOI: 10.1021/jp0453764
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study on the Reaction Mechanism of Proton Transfer in 2-Pyridone:  Effect of Hydration and Self-Association

Abstract: The proton-transfer mechanism in the isolated, mono, dehydrated forms and dimers of 2-pyridone and the effect of hydration or self-assistance on the transition state structures corresponding to proton transfer from the keto form to the enol form have been investigated using B3LYP and BH-LYP hybrid density functional methods at the 6-311++G (2d, 2p) basis set level. The barrier heights for both H2O-assisted and self-assisted reactions are significantly lower than that of the bare tautomerization reaction from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 56 publications
5
43
0
Order By: Relevance
“…The orbitals 35 (HOMO), 36 (LUMO), and 37 (LUMO+1) are respectively π and π* orbitals, while orbital 34 (n orbital) and orbitals 38, 39, and 40 (designated as Ryd 1 , 2, 3 ) are respectively non‐bonding and diffuse orbitals. Therefore the A‐, and B‐band absorption of NHP–(H 2 O) 2 cluster are respectively assigned to two π → π* transitions on the basis of our time‐dependent (TD)‐DFT computations and previous reported results . Two n → π* and three π → Ryd transitions are located, and they have negligible oscillator strength for the A‐ and B‐band absorptions.…”
Section: Resultssupporting
confidence: 51%
See 4 more Smart Citations
“…The orbitals 35 (HOMO), 36 (LUMO), and 37 (LUMO+1) are respectively π and π* orbitals, while orbital 34 (n orbital) and orbitals 38, 39, and 40 (designated as Ryd 1 , 2, 3 ) are respectively non‐bonding and diffuse orbitals. Therefore the A‐, and B‐band absorption of NHP–(H 2 O) 2 cluster are respectively assigned to two π → π* transitions on the basis of our time‐dependent (TD)‐DFT computations and previous reported results . Two n → π* and three π → Ryd transitions are located, and they have negligible oscillator strength for the A‐ and B‐band absorptions.…”
Section: Resultssupporting
confidence: 51%
“…The binding energies and structures of the mono‐ and double‐hydrated clusters of OHP and NHP were studied by using time‐of‐flight mass spectroscopy (TPFMS) and emission spectroscopy as well as ab initio calculations, and the results showed that the ground state hydrogen‐bonding energy for NHP–H 2 O and NHP–(H 2 O) 2 clusters are considerably larger than the corresponding OHP–H 2 O and OHP–(H 2 O) 2 clusters respectively . Density functional theory computations revealed that NHP–(H 2 O) 2 cluster is much more stable than NHP–H 2 O and OHP–H 2 O cluster . Our present combined experimental FT‐Raman spectroscopic and B3LYP/6‐311++G(d, p) computational results are in good agreement with the previous reported conclusion that NHP–(H 2 O) 2 cluster is the predominate species of NHP in water .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations